The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2494/photopolymer.28.319
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Reverse Mode Light Scattering Properties in Nematic Liquid Crystal Cell Using Polymer Stabilized Effect

Abstract: A coexistence with normal and reverse scattering modes is demonstrated in a single liquid crystal (LC) cell by using a polymer stabilized effect. The homogeneously oriented or twisted LC cell containing a small amount of reactive mesogen is exposed with UV light under a suitable curing voltage application. A light scattering state is obtained and it becomes clear by applying voltage. The cell fabricated without the curing voltage shows a reverse mode property, that is, a transparent voltage off-state and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Hysteresis in the transmission was therefore observed when increasing and decreasing the field in accordance with previous studies. [ 17–18 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hysteresis in the transmission was therefore observed when increasing and decreasing the field in accordance with previous studies. [ 17–18 ]…”
Section: Resultsmentioning
confidence: 99%
“…Hysteresis in the transmission was therefore observed when increasing and decreasing the field in accordance with previous studies. [17][18] Figure 2d,e shows the rise (scattering to transparent) and fall (transparent to scattering) times for the printed PSCLC droplet, respectively. These results were obtained when the printed droplet was subjected to a square wave signal with a 1 kHz frequency and an electric field of 5 V μm −1 , which as shown in Figure 2a-c result in the printed droplet becoming transparent.…”
Section: Electro-optic Characteristics Of Printed Psclc Dropletsmentioning
confidence: 99%
“…PNLCs can also be widely applied to various optical devices, such as light modulators, displays, and smart windows. [1][2][3][4][5][6][7][8][9][10][11]. PN-90 • twisted nematic LC (PN-90 • TNLC) cells have also extensively been studied [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The homogeneously aligned reverse mode cell using a photo reactive mesogen (RM) and LCs with positive dielectric constant anisotropy has been proposed by Hikmet [6,7]. We have also investigated reverse mode cells with different LC materials and orientations to reduce the driving voltage [8][9][10][11][12]. Those studies indicated that the polymer morphology control is key technology to reduce the voltage.…”
Section: Introductionmentioning
confidence: 99%